TINJAUAN YURIDIS PENERAPAN ASAS NON-SELF INCRIMINATION TERHADAP SAKSI MAHKOTA DALAM HUKUM ACARA PIDANA INDONESIA - Simanjuntak, Febri Nolin; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In criminal procedural law, witnesses can be divided into several forms, one of which is a crownwitness or a crown witness. The crown witness is a witness originating from or taken from one of the othersuspects or defendants who jointly committed a criminal act in the event that the witness was given a crown.Crown witnesses themselves are not regulated in detail in the Criminal Procedure Code. To be able to makea suspect or defendant as a crown witness must be carried out through the procedure of solving the case filewhich is the authority of the Public Prosecutor. The use of crown witnesses in uncovering a case still posesa problem, because the use of a crown witness is not in accordance with the system of evidence and themodel of the criminal justice system in force in Indonesia.The research entitled "The Application of the Principles of Non-Self Incrimination to CrownWitnesses in the Indonesian Criminal Procedure Code" aims to determine the application of the principle ofnon-self incrimination to crown witnesses and to describe the ideal arrangement for crown witnesses inIndonesian criminal procedure law.This research is normative research or library research. In this study, the authors chose research onlegal principles, namely the principle of non-self incrimination and comparison of law. The data used in thisstudy is secondary data. Then the data is analyzed qualitatively. The theoretical foundation used is thetheory of proof and the concept of the criminal justice system.The results of the study indicate that the application of the principle of non-self incrimination tocrown witnesses is not in accordance with the rules of law stipulated in the Indonesian Criminal ProcedureCode. This can be proven by a system of evidence adopted in Indonesia, where many legal rules regardingthe validity of an evidence in a criminal case are violated and there is a discrepancy between the existingcriminal justice system model and the rules governing the crown witnesses.Keywords : Non-Self Incrimination Principle, Witness Mahkota, Indonesian Criminal Procedure Code.